Perancangan UI/UX Aplikasi Smart Farming Pandailadang Dengan Metode Lean UX Berbasis Mobile Pada Desa Bringinbendo - Silvy Milda Puspita (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Indonesia is an agricultural country, where agriculture is a strong supporting sector in the development of the industrial sector. One of the subsectors in the agricultural sector is the food crops subsector. Bringinbendo Village is a village where the majority of the population are rice farmers, where rice farming is one type of food crop sub-sector. The amount of rice production over the last five years has fluctuated, but the rhythm tends to decrease. The causes of poor production results are rice pests and diseases, weather conditions, and incorrect fertilizer dosage. Apart from that, not all young people today are interested in becoming rice farmers and continuing their parents' profession. The method used in this thesis research is using the Lean UX method. Meanwhile, the method used in testing in this thesis research is using Heuristic Evaluation and System Usability Scale (SUS). The result of this research is to produce a PandaiLadang application design, which is a prototype of the PandaiLadang application design. The results of testing carried out by users with Heuristic Evaluation, obtained excellent and good qualifications. Meanwhile, testing using the System Usability Scale received a very good score, which means that the UI/UX design of the PandaiLadang application that has been created does not need to be repaired.